Cavern of the Fear / 1, Deltora Shadowlands. - Rodda, Emily (Rodda, Emily. Deltora shadowlands, 2002)
King Lief and his friends Barda and Jasmine go in search of a weapon powerful enough to combat the Shadow Lord's magic that is keeping thousands of their fellow Deltorans prisoner in the terrifying kingdom of Shadowlands.